Challenges of torrential flood risk management in Serbia - Petrović Ana M. (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
Torrential floods are the natural hydrological hazards manifesting as a consequence of extreme rainfall episodes which have a quick response from the watersheds of small areas, steep slopes and intensive soil erosion. Taking in consideration the nature of torrential flood (sudden and destructive occurrence) and the fact they are the most frequent natural hazards in Serbia, torrential flood risk management is a real challenge. Instead of partial solutions for flood protection, integrated torrential flood risk management is more meaningful and effective. The key steps should be an improvement of the legal framework on national level and an expansion of technical and biological torrent control works in river basins. Consequences for society can be significantly reduced if there is an efficient forecast and timely warning, rescue and evacuation and if affected population is educated about flood risks and measures which can be undertaken in case of emergency situation. In this paper, all aspects of torrential flood risk management are analyzed. [Projekat Ministarstva nauke Republike Srbije, br. 47007 III]